Sociologia e a esfera cultural contemporânea - Edson Silva de Farias (Universidade do Vale do Rio dos Sinos (UNISINOS), 2017)
This essay is intended to trace a panel showing how the complexity inherent to connections and sociocultural levels of integration, within a context of highly spread socialhuman interdependence, entails new qualities to circulations, to cultural and civilizatory encounters and crossroads. Therefore, it not only impacts the overall shape, content and dynamics of the cultural sphere, but it equally triggers reflective waves aiming at modes of cognition and socio-anthropological analytical inference procedures concerned with symbolization processes in production and use of cultural goods.